What Does Professional Digital Competence Mean in Teacher Education? - Andreas Lund; Anniken Furberg; Jonas Bakken; Kirsti Lyngvær Engelien (Universitetsforlaget, 2014)
Abstract The focus of this position paper is on the conceptualization of professional digital competence (PDC) in the teaching profession and its consequences for teacher education. The aim is to establish a concept that captures, challenges, and possibilities related to teaching and learning in technology-rich settings. By using three school subjects as cases, we argue the necessity of viewing PDC as comprising a deep understanding of technology, knowledge of students' learning processes, and an understanding of the specific disciplinary practices and features characterizing individual school subjects.